Characterization of p53 Family Homologs in Evolutionary Remote Branches of Holozoa - Bartas, Martin; Brázda, Václav; Červeň, Jiří; Pečinka, Petr (International journal of molecular sciences, 2019)
The p53 family of transcription factors plays key roles in development, genome stability, senescence and tumor development, and p53 is the most important tumor suppressor protein in humans. Although intensively investigated for many years, its initial evolutionary history is not yet fully elucidated. Using bioinformatic and structure prediction methods on current databases containing newly-sequenced genomes and transcriptomes, we present a detailed characterization of p53 family homologs in remote members of the Holozoa group, in the unicellular clades Filasterea, Ichthyosporea and Corallochytrea. Moreover, we show that these newly characterized homologous sequences contain domains that can form structures with high similarity to the human p53 family DNA-binding domain, and some also show similarities to the oligomerization and SAM domains. The presence of these remote homologs demonstrates an ancient origin of the p53 protein family.
Keywords: databáze genetické; Tumor Suppressor Protein p53; interakční proteinové domény a motivy; sekvenční homologie aminokyselin; Protein Interaction Domains and Motifs; Sequence Homology, Amino Acid; sekvence aminokyselin; multigenová rodina; introny; Introns; Evolution, Molecular; Amino Acid Sequence; molekulární evoluce; Databases, Genetic; Models, Molecular; Phylogeny; Protein Conformation; molekulární modely; Exons; nádorový supresorový protein p53; konformace proteinů; exony; fylogeneze; Multigene Family; Eukaryota